Homeownership, social capital and parental voice in schooling - Arthur Grimes; Steven Stillman; Chris Young (Institute for the Study of Labor (IZA), 2011)
We use New Zealand school board of trustees data to examine whether schools where parents have high rates of homeownership experience high parental voting turnout in elections. We also investigate whether homeownership influences the probability that a school board proceeds to election, indicating parental willingness to serve as a school trustee. Similarly, we examine whether state-owned social housing rates affect these outcomes. We compile results initially without controlling for other factors, and then controlling for a wide range of other characteristics, to test the robustness of simple observed associations between homeownership and state-ownership rates and outcome variables. Our findings show no discernible effect of homeownership on parental voting turnout in school elections after controls are added (contrary to the simple positive association), but a (robust) positive impact of both homeownership and state-ownership rates on the probability that a school holds an election.
urn:nbn:de:101:1-201201102990
Keywords: I28; R23; Z13; 330; homeownership; school elections; parental voice; social capital; Wohneigentum; Bürgerbeteiligung; Eltern; Allgemeinbildende Schule; Social Capital; Neuseeland